Streptococcal Extracellular Membrane Vesicles Are Rapidly Internalized by Immune Cells and Alter Their Cytokine Release - Mehanny, Mina; Koch, Marcus; Lehr, Claus-Michael; Fuhrmann, Gregor (Frontiers in Immunology, 2020)
Extracellular vesicles are membranous structures shed by almost every living cell. Bacterial gram-negative outer membrane vesicles (OMVs) and gram-positive membrane vesicles (MVs) play important roles in adaptation to surrounding environment, cellular components exchange, transfer of antigens and virulence factors, and infection propagation. Streptococcus pneumoniae is considered one of the priority pathogens, with a global health impact due to increasing infection burden and growing antibiotic resistance. We isolated MVs produced from Streptococcus pneumoniae reference strain (R6), and purified them via size exclusion chromatography (SEC) to remove soluble protein impurities. We characterized the isolated MVs by nanoparticle tracking analysis (NTA), and measured their particle size distribution and concentration. Isolated MVs showed a mean particle size range of 130-160 nm and a particle yield of around 1012 particle/mL. Cryogenic transmission electron microscopy (cryo-TEM) images revealed a very heterogeneous nature of isolated MVs with a broad size range and various morphologies, arrangements and contents. We incubated streptococcal MVs with several mammalian somatic cells, namely human lung epithelial A549 and human keratinocytes HaCaT cell lines, and immune cells including differentiated macrophage-like dTHP-1 and murine dendritic DC2.4 cell lines. All cell lines displayed excellent viability profile and negligible cytotoxicity after 24 h incubation with MVs at concentrations reaching 106 MV/cell (somatic cells) and 105 MV/cell (immune cells). We evaluated uptake of fluorescently labelled MVs into these four cell lines, using flow cytometry and confocal microscopy. Dendritic cells demonstrated prompt uptake after 30-minute incubation, whereas other cell lines showed increasing uptake after 2 h incubation and almost complete colocalization/internalization of MVs after only 4 h incubation. We assessed the influence of streptococcal MVs on antigen presenting cells e.g., dendritic cells using enzyme-linked immunosorbent assay (ELISA), and observed enhanced release of TNF-α, slight increase of Interleukin-10 (IL-10) secretion and no detectable effect on IL-12. Our study provides better understanding of gram-positive streptococcal MVs, and show their potential to elicit a protective immune response. Therefore, they could offer an innovative avenue for safe and effective cell-free vaccination against pneumococcal infections.